Peran Kurikulum Merdeka Dalam Peningkatan Kualitas Anak Didik Untuk Menuju Indonesia Emas 2045 - Muhartono, Djoko Siswanto; Nur Laili, Alivia Novita; Prangdicha, Bryant; Anggaini, Veronika Kiky (Institut Riset dan Pengembangan Indonesia, 2024)
This study aims to analyze the role of the independent curriculum in improving the quality of students and identify the positive impact of the implementation of the independent curriculum on the achievement of learning and the quality of students towards a Golden Indonesia 2045 at SDN Banyu Urip 3, Surabaya City. The data sources related to the Independent Curriculum, student learning outcome reports, and data on the profile of SDN Banyu Urip 3, Surabaya City. The data collection techniques used are documentation, interviews, and observations. The data analysis using qualitative. The findings of this study is presented based on the analysis of data obtained that the implementation of the Independent Curriculum has a positive impact on students' learning achievement and character, including improving students' critical thinking skills, creativity, and communication. The conclusion of this study will be formulated based on data analysis and the findings obtained are that the Independent Curriculum at SDN Banyu Urip 3 can form a profile of Pancasila students who are ready to face the challenges of global competition in achieving the vision of Golden Indonesia 2045 by creating quality, competent, and highly competitive human resources.